Radiographic spinopelvic parameters in skeletally mature patients with Scheuermann disease - Tyrakowski, Marcin; Mardjetko, Steven; Siemionow, Kris (Spine (Philadelphia, Pa. 1976), 2014)
Retrospective radiographical analysis of sagittal spinopelvic parameters in skeletally mature patients with Scheuermann disease (SD). To analyze anatomical and positional parameters of spinopelvic sagittal alignment in mature patients with SD. Sagittal spinopelvic alignment has already been characterized in normal subjects and deviations in sagittal parameters have been reported for various spinal pathologies. No study has investigated spinopelvic parameters in SD. Standing posteroanterior and lateral radiographs of the skeletally mature patients with SD were analyzed. Immature patients and those with other spinal pathologies were excluded from the study. Pelvic positional and anatomic parameters and spinal parameters were measured. Pelvic incidence (PI) was compared with the values reported for healthy individuals. Correlations between the measured parameters were analyzed. Forty patients met the inclusion criteria. Sixteen females and 24 males (mean age, 25 yr) were analyzed. The mean PI in this group was 40° and was significantly lower than that reported for healthy adults and adolescents (P < 0.0001) and not significantly different than the values reported for healthy children (P = 0.44). Patients with atypical (thoracolumbar) SD had lower PI than those with typical (thoracic) form (41° vs. 38°; P = 0.09). There was no correlation between PI and LL, thoracic kyphosis, or thoracolumbar kyphosis. This study demonstrated that skeletally mature patients with SD have significantly lower PI than healthy adults. There was no correlation between PI and LL in individuals with SD. This challenges the role of PI in predicting the proper values of LL in this group of patients. Further studies are needed to investigate whether impaired spinopelvic alignment is a cause or a result of SD. 3.